Economic Empowerment and Community Resilience through the Development of Lejja Tourism Villages: Impact Analysis, Participation, and Sustainability - Heriani Heriani; Andy Mulyana; Retnaningtyas Susanti; Yusrafiddin Yusrafiddin; Rinda Novianti; Rahmad Purnama (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the economic impact, level of community participation, and sustainability challenges in the development of Lejja Tourism Village, Soppeng Regency, as a community-based tourism model. The approach used is qualitative with data collection techniques through in-depth interviews, participatory observations, and documentation studies. Data were analyzed using open coding methods to identify key themes emerging from the experiences of communities and local stakeholders. The results of the study show that tourism development in Lejja has a positive economic impact in the form of income diversification, the growth of local culinary and handicraft businesses, and the increasing role of village institutions such as BUMDes. However, these economic benefits have not been evenly distributed due to limited access to capital and differences in geographical positions between village areas. The level of community participation is still dominant at the implementation stage, while involvement in strategic decision-making is still low due to the top-down governance model. In addition, sustainability challenges arise such as increasing waste volume and decreasing hot water discharge that demand the application of the triple bottom line principle in environmental governance. On the other hand, communities show high adaptive capacity through social solidarity and local business innovation that can maintain economic resilience during times of crisis. This study concludes that the development of Lejja Tourism Village can be an instrument for economic empowerment and community resilience if managed through collaborative governance, strengthening human resource capacity, and inclusive and sustainable tourism policies. These findings enrich the literature on community-based tourism in rural Indonesia’s context and provide practical recommendations for local governments and village institutions in strengthening local economies based on sustainable tourism.